Campaign Spending with Impressionable Voters - Rebecca B. Morton; Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
We consider a model of two-candidate elections with a one-dimensional policy space. Spending on campaign advertisements can directly influence voters' preferences, and contributors give the money for campaign spending in exchange for promised services if the candidate wins. we find that the winner of the election depends crucially on the contributors' beliefs about who is likely to win, and the contribution market tends towards nonsymmetric equilibria in which one of the two candidates has no chance of winning. If the voters are only weakly influenced by advertising or if permissible campaign spending is small, then the candidates choose policies close to the median voter's ideal point, but the contributors still determine the winner. Uncertainty about the Condorcet-winning point (or its nonexistence) can change these results and generate equilibria in which both candidates have substantial probabilities of winning.
Keywords: 330